The Concept of Transformation on Pandan Mat Weaving Art - Norazlina Subani; Umi Huda Mohd Abdullah; Faezah Baridah Zulfikri (Kolej Genius Insan, USIM, 2024)
E-Proceedings 3rd Insan Junior Researchers International Conference 2022 (iJURECON 2022) : "STREAM for a better future”/Editors: Rahayu Ahmad, Muhammad Azan Tamar Jaya, Ahmad Fuad Mohamad Amin, Nur Aisyah Mohamed, Nur Fatin Fathillah Mazlan. 21-23rd October 2022 (Virtual Conference) Organized By : Kolej Genius Insan,USIM